The Opportunities and Controversies of Reversible Computing. - DeBenedictis, Erik P.; Mee, Jesse K.; Frank, Michael P. (Computer (00189162), 2017)
Industry's inability to reduce logic gates' energy consumption is slowing growth in an important part of the worldwide economy. Some scientists argue that alternative approaches could greatly reduce energy consumption. These approaches entail myriad technical and political issues.